Pengaruh Jumlah Tanggungan Keluarga dan Pendapatan Terhadap Tingkat Pendidikan Anak pada Desa Rejosari Kecamatan Lirik Kabupaten Indragiri Hulu - Aris Triyono; Fatti Corrina; Eka Saputri; Tri Rahayu (Universitas Batanghari, 2022)
This research was conducted on Rejosari Village,Lyrics District. In this study, whether the number of family dependents has an effect on the level of education of children in Rejosari Village,Lyrics District. Does income affect the level of education of children in Rejosari Village,Lyrics District. The purpose of the study was to determine the effect of the variable Number of Family Dependents and Income on the Education Level of Children in Rejosari Village,Lyrics District. Sampling was done by accidental sampling randomly with 115 sample as respondents. The analytical method used is descriptive quantitative method, data analysis is carried out by path analysis (with the help of the IBM SPSS Stastic version 21.0 program). From the results of the study showed that the number of family dependents and income had an effect on the level of education of children in Rejosari Village,Lyrics District. The number of family dependents affects the level of children's education in Rejosari Village,Lyrics District. Income affects the level of education of children in Rejosari Village,Lyrics District